Antioxidant Activity and Phytochemicals of Locally Consumed Plant Foods from Baguio City, Philippines - Paolo Robert P. Bueno; Rachel Camille R. Cabrera; Gracia Fe B. Yu (Borneo Journal of Pharmacy, 2023)
In the Philippines, Baguio City – known as the “City of Pines” – holds the country’s major source of temperate climate vegetables. With increased dietary awareness, the consumption of plant foods rich in antioxidants has become relevant. Twenty-nine methanolic extracts from Baguio-produced plant foods were evaluated for antioxidant potential using DPPH, ferric reduction antioxidant power (FRAP), metal chelation, superoxide anion, nitric oxide, hydroxyl radical scavenging activities, MTT reduction, and phytochemical tests. Fagopyrum tataricum leaves, Vaccinium myrtoides fruit, and Morus alba fruit showed the most effective DPP radical, concentration-dependent reducing power, but low metal chelating activity. Solanum tuberosum tuber (22.86±63.26%) showed effective concentration-dependent chelating activity at 125 μg/mL. Citrus aurantium fruit (26.77±9.24%) and Raphanus raphanistrum root (41.13±0.11%) demonstrated an effective scavenging activity against superoxide anions at 45.5 μg/mL. Significant nitric oxide scavenging activity was observed in some fruits. Brassica oleracea Cab leaves (54.36 ± 2.38%) showed the highest inhibitory activity against hydroxyl radicals at 166.7 μg/mL. Phytochemical analyses showed that most plant samples revealed the presence of glycosides, terpenes/terpenoids, and steroids/phytosterols, while few contained phenolic and tannin components. These phytochemicals may explain the dual behavior as an antioxidant or a prooxidant observed. Thus, determining food antioxidant component types and their concentration is necessary to maximize the potential to scavenge oxidants.